Label-Free Enrichment of Highly Metastatic Tumor-Initiating Cells up to a Monoclonal State - Ciaramicoli, Larissa M.; Kwon, Haw-Young; Im, Chun Y.; Kim, Namhui; Oh, Yoojin; Chang, Young-Tae; Kang, Nam-Young (Biomaterials research, 2025)
IntroductionCancer stem cells (CSCs) are a subpopulation of cancer cells with self-renewal capabilities, tumor initiation properties, and differentiation abilities, which drive tumor growth, metastasis, and recurrence [1,2]. Depleting CSCs in tumors has been shown to inhibit cancer metastasis, implicating their primary role in cancer resistance [3–6]. Therefore, targeting CSCs may be key to preventing tumor spread. Most tumor cells cannot form a new tumor when transplanted into a nontumor site or another body. The ability of CSCs to generate new tumors shares some features with embryonic stem cells, but they have different appearances [7,8]. To avoid a possible misconception, the term CSC has been replaced with tumor-initiating cells (TICs). Identifying and isolating TICs has proven challenging because they do not have a standard biomarker and mostly overlap with normal stem cell markers. Therefore, multidimensional techniques are required for their isolation: a fluorescent approach, such as immunochemistry, side population assay, or fluorescent probes, followed by 3-dimensional sphere culture [9–18]. Culturing TICs using a sphere formation assay is conducted under nonadherent and serum-free conditions [19], allowing for cell-to-cell attachment while leading differentiated tumor cells to undergo apoptosis [20]. However, the method does not guarantee the purity of the cells [21]. Depending on the application of TIC analysis in vitro, a purified population may be required. We propose a label-free method to enrich an aggressive TIC population, which shows high expression levels of TIC/metastasis markers (CD44 and CD54), and demonstrate improved tumor formation as well as metastasis in lung and thyroid cancer in xenograft models. KCI Citation Count: 0